2014
DOI: 10.1039/c4ra05907g
|View full text |Cite
|
Sign up to set email alerts
|

Templated magnesiothermic synthesis of silicon nanotube bundles and their electrochemical performances in lithium ion batteries

Abstract: Silicon nanotube bundles (Si NBs) have been synthesized on a large scale via a templated magnesiothermic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…[12][13][14][15][16] Currently, Si-NT are mainly prepared by chemical vapor deposition (CVD) or template-assisted methods. [12,[17][18][19][20][21][22][23][24][25][26][27][28] However, the usage of toxic SiH 4 /SiCl 4 as raw materials and expensive gold as catalysts as well as the low production yield largely restrict the large-scale deployment of the CVD methods. [19][20][21]23] The template-assisted strategy requires tedious procedures including the construction of sacrificial templates, coating of Sicontaining precursors, extraction of Si, and removal of inner template.…”
Section: Doi: 101002/advs202001492mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] Currently, Si-NT are mainly prepared by chemical vapor deposition (CVD) or template-assisted methods. [12,[17][18][19][20][21][22][23][24][25][26][27][28] However, the usage of toxic SiH 4 /SiCl 4 as raw materials and expensive gold as catalysts as well as the low production yield largely restrict the large-scale deployment of the CVD methods. [19][20][21]23] The template-assisted strategy requires tedious procedures including the construction of sacrificial templates, coating of Sicontaining precursors, extraction of Si, and removal of inner template.…”
Section: Doi: 101002/advs202001492mentioning
confidence: 99%
“…[19][20][21]23] The template-assisted strategy requires tedious procedures including the construction of sacrificial templates, coating of Sicontaining precursors, extraction of Si, and removal of inner template. [12,[22][23][24][25][26][27][28] The preparation procedures become more complicated when an extra surface layer is coated via post-processing strategies to improve the performance of Si-NT. [11,29,30] Exploring practical methods for large-scale and low-cost preparation of Si-NT from affordable silicon sources as well as in situ coating strategy is an appealing but tough task.…”
Section: Doi: 101002/advs202001492mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructured silicon ranging from nanowires, nanofilms, nanotubes to nanoparticles and their composites, in which the strain can be relaxed easily without mechanical fracture because of their smaller size and available surrounding free spaces, have been exploited widely to alleviate the structure deterioration efficiently [6][7][8][9][10]. Si nanotube bundles (NBs) have been successfully synthesized at large scale in our previous work [11] via a magnesiothermic reduction method [12]. However, structural collapse still occurred during prolonged electrochemical reactions for these long Si tubes with length larger than several micrometers, hence resulting in unsatisfactory electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…To address these drawbacks, one approachi st he fabrication of silicon-basedm aterials with variousn anoscale structures, such as nanospheres, [10,11] nanotubes, [12][13][14] nanowires, [15,16] and porouss tructures, [17,18] which have been explored previously.I t has been demonstrated that nanostructures of silicon-based materials shorten the pathway lengths of the lithium ions, increase the electrode-electrolyte contact area, and accommodate large volume changes,l eadingt oi mproved anode performances. In particular, as one of the advantages of porous materials tructures, [19] the porosity of silicon-basedm aterials provides as uperior configuration for accommodating volume changes and facilitatese lectron and ion transfer.H owever, the cycling performances of silicon-based anodesa re still limited by the introduction of only nanoscale structural features.…”
Section: Introductionmentioning
confidence: 99%